Representasi Kekerasan pada Perempuan dalam Video Klip Tak Mau Berubah-Kesha Ratuliu - M. Andre Ardiansyah; Nani Kurniasari (UNIVERSITAS KALBIS, 2022)
Kesha Ratuliu's video clip “Tak Mau Berubah” shows and depicts violence against women. The purpose of this research is to find out the representations of violence against women that occurs in Kesha Ratuliu's video clip